2017
DOI: 10.1080/10255842.2017.1322072
|View full text |Cite
|
Sign up to set email alerts
|

Influences of geometrical and mechanical properties of bone tissues in mandible behaviour – experimental and numerical predictions

Abstract: The properties and geometry of bone in the mandible play a key role in mandible behaviour during a person's lifetime, and attention needs to be paid to the influence of bone properties. We analysed the effect of bone geometry, size and bone properties in mandible behaviour, experimenting on cadaveric mandibles and FE models. The study was developed using the geometry of a cadaveric mandible without teeth. Three models of cadaveric condyles were experimentally tested with instrumented with four rosettes, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…Strain gauge was a simple procedure to evaluate the stress distribution in the cortical bone [ 10 ]. We defined 10 points around the acetabulum as depicted in Fig 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Strain gauge was a simple procedure to evaluate the stress distribution in the cortical bone [ 10 ]. We defined 10 points around the acetabulum as depicted in Fig 5 .…”
Section: Methodsmentioning
confidence: 99%
“…We find that five of the selected studies had a PR of 0.3 or close to it (Gröning et al, 2009;Ramos et al, 2017Ramos et al, , 2019. Clason et al (2004) Ramos et al, 2017). The effect of which is expected to be marginal.…”
Section: Bone Geometry and Property Acquisitionmentioning
confidence: 70%
“…The studies that mechanically tested the PR of the mandible in different directions showed values ranging from 0.18 to 0.53 (Dechow et al, 1993;Schwartz-Dabney & Dechow, 2003). We find that five of the selected studies had a PR of 0.3 or close to it (Gröning et al, 2009;Ramos et al, 2017Ramos et al, , 2019. Clason et al (2004) Ramos et al, 2017).…”
Section: Bone Geometry and Property Acquisitionmentioning
confidence: 79%
See 1 more Smart Citation
“…The biomechanics session presented work in progress based on research performed in centers that have traditionally studied the TMJ by developing pioneering methods [14][15][16][17][18]. New data obtained on larger subject samples are providing foundational data showing different loading patterns for different diagnostic groups, in particular, those with myogenous and arthrogenic pain.…”
Section: Biomechanics Sessionmentioning
confidence: 99%